Not on my watch: (Re)clamations of my Tshimanda, my identity, my language - Mandende, I. P.; Sebola, M.; Mudau, M. L.; Ndhobela, A. J. (South African Journal of Higher Education, 2024)
The standardisation process of a language is always a polemic undertaking, and Tshivenḓa is no exception. This article explores the Tshivenḓa dialects and the standardisation process that this language went through. The importance of language as a primary resource for an individual, social identification, and also as a means of learning and communication, cannot be overemphasised. Moreover, when different language varieties come into contact, acculturation is inevitable, i.e., linguistic and cultural elements from both sides will diffuse and “contaminate” each other’s languages and culture. However, this phenomenon is not fully researched, especially among the Tshivenḓa dialects. The lexicographers and terminographers, who are tasked with the development and maintenance of the Tshivenḓa language, seem to be “trapped” in the colonial and apartheid era, i.e., of selecting and elevating one dialect over others to represent a language. Since 1994, the year of the dawn of a democratic dispensation in South Africa, this process has proceeded at a snail’s pace. In this study, a qualitative, ethnographic approach was adopted, and data were collected through telephonic interviews, where six participants were purposefully and conveniently sampled. The findings of this study may benefit speakers of Tshivenḓa, lexicographers, terminographers, and all language practitioners, teachers, and learners. When people value their language and heritage, use it often without prejudice or hesitancy, and practice their culture and traditions, their identity, history, dignity, and heritage become preserved. Tshivenḓa, at the official level, may have many lexical items in its endeavour to carry out its function as an official language in different domains.